Losses and orbital part of the Poynting vector of air-core modes in hollow-core fibers - G.K. Alagashev; S.S. Stafeev; A.D. Pryamikov (Компьютерная оптика)
In our earlier works, we investigated a relationship between the formation of vortices in the transverse component of the Poynting vector of core modes and the regimes of strong localization of these modes in solid core micro-structured optical fibers. In this paper, we consider the behavior of the orbital part of the Poynting vector of fundamental and high-order modes in hollow-core fibers, and make comparisons with similar fundamental core mode behavior in solid core micro-structured optical fibers. We then demonstrated the impact of the “negative” curvature of the core-cladding boundary of a hollow-core fiber on the behavior of the orbital part of the Poynting vector of the air-core modes.